IMPROVING STUDENTS’ WRITING SKILL BY APPLYING GROUPING TECHNIQUE AT SEVENTH GRADE OF THE STATE ISLAMIC JUNIOR HIGH SCHOOL BUSTANUL HUDA PAGAR PUDING TEBO JAMBI (NUR EL-ISLAM : Jurnal Pendidikan dan Sosial Keagamaan, 2017)
This research discusses about the use of Grouping Technique to students learning outcomes in English subjects at Islamic Junior High School Bustanul Huda Pagar Puding Tebo Jambi. This study is Classroom Action Research (CAR) by applying grouping technique, while collecting data using observation technique, field note, Questionnaire, and test. It was found that applying grouping technique can improve the students’ result of writing skill in Islamic Junior High School Bustanul Huda Pagar Puding Tebo Jambi. The result of this study suggests that English teacher apply the Grouping Technique in learning writing. Keywords: Grouping Technique, English, Student Achievement